Hand hygiene knowledge, perception and practice of healthcare workers in a Turkish university hospital intensive care unit - BİLGİN, HÜSEYİN; AY, NADİYE PINAR; HIDIROĞLU, SEYHAN; SİLİ, ULUHAN; KORTEN, VOLKAN (J INFECTION DEVELOPING COUNTRIES, 2019)
Introduction: While improvement of hand hygiene (HH) compliance is considered as the best approach to reduce healthcare-associated infections, the instructional interventions in HH among healthcare workers of intensive care unit (ICU) of our hospital was not successful enough. The following study was conducted to evaluate HH knowledge, perception, practice and effectiveness of the trainings among healthcare workers of ICU in our hospital. Methodology: A cross-sectional study was conducted in the ICU containing 8 medical and 16 surgical beds with 284 filled questionnaires about HH knowledge and 1187 observed opportunities for HH compliance. Results: Overall observed HH compliance rate was 40.6%; lowest compliance was 21.7% for before clean/aseptic procedure indication and highest compliance was 68.6% for after touching a patient indication. Although > 90% healthcare workers correctly identified the World Health Organization's five indications for HH, 82 -85% failed to recognize non-indications, i.e. when it was not necessary to perform HH. Our study showed that 15.1% of healthcare workers neither received nor felt the need for HH training. Conclusions: Despite regular HH trainings, healthcare workers could not differentiate when HH was not required which suggested failure to understand HH rationale. This may explain poor HH compliance rates. A systematic study is needed in order to find out the reasons behind of this noncompliance and improve HH training methods for educating healthcare workers.
Keywords: Hand hygiene compliance; quantitative study; healthcare-associated infections; intensive care unit